Philisophy and theory of law - Yeon, Asmah Laili; Yusof, Yuhanif (Universiti Utara Malaysia, 2015)
Understanding of the philosophy and theory behind the law is significance to law makers, legal practitioners, academicians and laymen.The rationales are to have some understanding of public policy and the real aim of the laws that made up particular practices or the root of practices.Therefore, this book highlight selected philosophy and theory of laws in the area of commercial, financial and corporate law; medical law; constitutional and administrative law and lastly human resource law.The massive information and knowledge in this book will benefits law makers, legal practitioners, academicians, universities students in understanding the philosophy and theory of the law first, before appreciating and applying the substantive law in their profession and life.